2021
DOI: 10.1096/fj.202100827r
|View full text |Cite
|
Sign up to set email alerts
|

8‐ iso ‐prostaglandin E 2 induces nasal obstruction via thromboxane receptor in murine model of allergic rhinitis

Abstract: Thromboxane receptor (TP) mediates nasal obstruction, a typical symptom of allergic rhinitis. Since it has been reported that several types of eicosanoids, such as non-enzymatic oxidation product of arachidonic acid isoprostane, act as a TP ligand, there is a possibility that some other eicosanoids contribute to the TPmediated nasal obstruction. The aim of this study is to investigate the mechanisms of TP-mediated nasal obstruction. Intranasal challenges of ovalbumin (OVA) induced nasal obstruction in mice. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…We previously revealed that 10-time OVA stimulation induced eosinophil infiltration in nasal mucosa of BALB/c mice (Vehicle: 0.03 ± 0.01 × 10 3 cells/mm 2 , OVA: 4.15 ± 1.16 × 10 3 cells/mm 2 ). 21 We also found that the 10-time OVA stimulation induced neutrophil infiltration in nasal mucosa (Vehicle: 25.98 ± 9.75 × 10 3 cells/ mm 2 , OVA: 43.70 ± 11.31 × 10 3 cells/mm 2 , Figure 1F). We collected NALF 30 min after stimulation with OVA 10 times and measured the amount of lipid metabolites using LC-MS/MS.…”
Section: Ar Model Micesupporting
confidence: 57%
See 1 more Smart Citation
“…We previously revealed that 10-time OVA stimulation induced eosinophil infiltration in nasal mucosa of BALB/c mice (Vehicle: 0.03 ± 0.01 × 10 3 cells/mm 2 , OVA: 4.15 ± 1.16 × 10 3 cells/mm 2 ). 21 We also found that the 10-time OVA stimulation induced neutrophil infiltration in nasal mucosa (Vehicle: 25.98 ± 9.75 × 10 3 cells/ mm 2 , OVA: 43.70 ± 11.31 × 10 3 cells/mm 2 , Figure 1F). We collected NALF 30 min after stimulation with OVA 10 times and measured the amount of lipid metabolites using LC-MS/MS.…”
Section: Ar Model Micesupporting
confidence: 57%
“…Figure 1E shows the representative image of nasal mucosa. We previously revealed that 10‐time OVA stimulation induced eosinophil infiltration in nasal mucosa of BALB/c mice (Vehicle: 0.03 ± 0.01 × 10 3 cells/mm 2 , OVA: 4.15 ± 1.16 × 10 3 cells/mm 2 ) 21 . We also found that the 10‐time OVA stimulation induced neutrophil infiltration in nasal mucosa (Vehicle: 25.98 ± 9.75 × 10 3 cells/mm 2 , OVA: 43.70 ± 11.31 × 10 3 cells/mm 2 , Figure 1F).…”
Section: Resultsmentioning
confidence: 99%